THE INFLUENCE OF BREEDER BEHAVIOR ON LOCAL DUCK (Anas Domesticus) INCOME IN LANGSA LAMA DISTRICT, LANGSA CITY - Miftahul Jannah; Kiagus M. Zain Basriwijaya; Hanisah (Bajang Institute, 2023)
This study aims to analyze the effect of farmer behavior on the income of local duck farmers in Langsa Lama District, Langsa City. The sampling technique used purposive sampling technique with a total sample of 39 people. The data used in this study are primary data and secondary data. To determine the effect of farmer behavior on the income of local duck farmers in Langsa Lama District, Langsa City, statistical analysis was used with multiple linear regression methods. Data processing is carried out using SPSS software. The results of this study indicate that the attitude variable has a significant effect on the income of local duck farmers in the Langsa Lama District, Langsa City, the skill variable has a very significant effect on the income of local duck farmers in the Langsa Lama District, Langsa City, and the knowledge variable has no significant effect on the income of local duck farmers in the Langsa Lama District, Langsa City.